An Investiogation on the antecedents influencing customer e-loyality and e-satisfaction among Malaysians with the effects of trustworthiness - Wong, Winnie Poh Ming (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The rapid growth of online shopping has led to increasing interest in how to inspire customer e-loyalty and e-satisfaction in Malaysia context. The general objective of this study is to explore and examine the perceptions of Malaysian Internet users that contribute to customer e-loyalty and e-satisfaction. Specifically, the purpose of this study is to (a) identify the most significant determinants of customer e-loyalty and e-satisfaction; (b) investigate the strength of relationships between customer interface quality, website quality, service quality, technology acceptance factors, and technology trust and customer e-loyalty and e-satisfaction; (c) examine the effect of trustworthiness on customer e-loyalty and e-satisfaction; and lastly (d) investigate the effect of trustworthiness on customer interface quality, website quality, service quality, technology acceptance factors, and technology trust and customer e-loyalty and e-satisfaction. The current research differs from previous studies by investigating various dimensions of customer interface quality, service quality, website quality, technology acceptance factors, and technology trust with the outcome of behavioral intentions, namely customer e-loyalty (measured by word-of-mouth, future purchase intentions, and complaining behavior) and e-satisfaction (measured by repurchase intention and revisit intention). This study also examines the indirect effect of customer interface quality, website quality, service quality, technology acceptance factors, and technology trust on customer e-loyalty and e-satisfaction through trustworthiness. Specifically, this study is perhaps the first to test trustworthiness as the mediator to measure the Malaysian Internet users’ behavioral intentions. A quantitative survey was conducted among Malaysian Internet users who have experience in accessing the Internet and Internet shopping. To participate, they had to have carried out at least one online transaction and made an e-purchase in the previous three months. The theoretical framework for the current study was developed from previous research. SPSS statistical software and SmartPLS 2.0 (M3) were used as the main analytical tools to establish the results in order to address the research objectives. A total of 395 respondents participated in this study. This study is perhaps the first to propose and validate a new model set of variables for customer e-loyalty and e-satisfaction among Malaysians in the Internet environment. The current findings of the study may be informative, and act as a basis for future researchers who are interested in an online study in Malaysia. Practically, the findings may also assist Malaysian e-retailers in understanding the key factors of business-to-consumer interactions and how to capture more online shoppers. In particular, this research details the area of trustworthiness in the online context. Some of the implications, limitations of the study, and recommendations for future research are outlined in the current study.